태풍사전방재모델의 예측 정확도 향상을 위한 연구 Part II: GDAPS, RDAPS, GFS 자료별 WRF 민감도 분석 - 나하나(Hana Na); 정우식(Woo-Sik Jung) (한국대기환경학회지(국문), 2020)
Typhoon Disaster Prevention Model was developed and operated to reduce damage caused by typhoons that hit the Korean Peninsula. In this study, the sensitivity analysis of the initial meteorological input data of the WRF modeling, which produce the input data of the Typhoon Disaster Prevention Model, was carried out as a study to improve the accuracy of the Typhoon Disaster Prevention Model. As a result of comparing the simulation of the raw data with the typhoon track and the central pressure, it was found that the central pressure of the typhoon was well simulated in the order of GDAPS, GFS, and RDAPS. For wind speed, the results using GDAPS as the initial input data were best simulated, followed by RDAPS and GFS. 3-Second gust produced by the Typhoon Disaster Prevention Model also showed good results in the order of GDAPS, RDAPS and GFS. KCI Citation Count: 0